Synthesis of gold nanospheres and nanotriangles by the Turkevich approach - Shankar, S. S.; Bhargava, S.; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2005)
Gold nanoparticles of triangular morphology possess interesting optical properties with potential application in medicine and infrared absorbing coatings, however, little is known about conditions that favor their growth. In this paper, we have reinvestigated a time-tested recipe for the formation of gold nanospheres by citrate reduction of aqueous gold ions under boiling conditions (Turkevich recipe). Our principle findings are that gold nanotriangle formation is kinetically controlled and is highly favored at low temperatures. Furthermore, the presence of chloride ions from the precursor chloroaurate ions plays a major role in promoting the growth of [111] oriented triangular/truncated triangular particles. The presence of bromide and iodide ions that possess the ability to replace surface-bound chloride ions inhibits triangle formation to varying degrees.
Keywords: Crystal growth; Gold; halides; nanospheres; nanotriangles; Temperature effect